Future State : Wonder Woman - McKinney, L. L. (Leatrice L.); Jones, Joëlle; Watters, Dan; Cloonan, Becky; Conrad, Michael W. (DC Comics, 2021)
"Who is Wonder Woman? Future State: Wonder Woman follows the stories of three wonder-filled women, Maria Flor, Nubia, and Diana Prince. Maria Flor will face off against the forces of hell, while Nubia leads a squad of Amazons far from Paradise Island. And Diana Prince is ready to fight for the world until the very end."--